Osseointegration for Lower-Extremity Amputees: Operative Considerations from the Plastic Surgeon's Perspective. Issue 11 (2nd November 2022) - Vernice, Nicholas A.; Askinas, Carly A.; Black, Grant G.; Truong, Albert Y.; Reif, Taylor J.; Rozbruch, S. Robert; Otterburn, David M.
Abstract : ➢ Osseointegration for lower-extremity amputees, while increasing in frequency, remains in its relative infancy compared with traditional socket-based prostheses. ➢ Ideal candidates for osseointegration have documented failure of a traditional prosthesis and should be skeletally mature, have adequate bone stock, demonstrate an ability to adhere to a longitudinal rehabilitation protocol, and be in an otherwise good state of health. ➢ Lowering the reoperation rate for soft-tissue complications depends heavily on surgical technique and on the implant device itself; the current gold standard involves a smooth implant surface for dermal contact as well as maximal skin resection to prevent skin breakdown against the prosthesis. This may include the need for thighplasty to optimize skin reduction. ➢ Interdisciplinary peripheral nerve management, such as targeted muscle reinnervation, performed in tandem with a plastic surgery team can treat existing and prevent future symptomatic neuromas, ultimately improving pain outcomes.